The influence of the school environment through school culture on motivation to learn the subject of faith and morals at MTs Al Khairaat Kwandang - Maghfira Aulia Zainuddin; Kasim Yahiji; Apriliyanus Rakhmadi Pratama (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The purpose of this study is to examine how the school environment influences students' desire to learn about Akidah Akhlak at MTs Al-Khairaat Kwandang, both directly and indirectly through school culture as an intervening variable. This study employed a quantitative, correlational research design. Data wer collected via a closed-ended questionnaire distributed to 138 students. Simple random sampling was used to gather the data. Data analysis was conducted to determine the relationships among the study variables using descriptive statistics and path analysis. The results of the study indicate that the school environment has a positive influence on students' motivation to learn, both directly and through school culture. A positive school culture has the ability to foster a positive learning environment, which in turn can strengthen students' desire to study Akidah Akhlak Therefore, it can be concluded that improvements to the school culture and environment at MTs Al-Khairaat Kwandang play a significant role in enhancing students' motivation to learn.